Platelets and COVID-19 - Rohlfing, Anne-Katrin; Rath, Dominik; Geisler, Tobias; Gawaz, Meinrad (Hämostaseologie, 2021)
In 2019 first reports about a new human coronavirus emerged, which causes common cold symptoms as well as acute respiratory distress syndrome. The virus was identified as severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and severe thrombotic events including deep vein thrombosis, pulmonary embolism, and microthrombi emerged as additional symptoms. Heart failure, myocardial infarction, myocarditis, and stroke have also been observed. As main mediator of thrombus formation, platelets became one of the key aspects in SARS-CoV-2 research. Platelets may also directly interact with SARS-CoV-2 and have been shown to carry the SARS-CoV-2 virus. Platelets can also facilitate the virus uptake by secretion of the subtilisin-like proprotein convertase furin. Cleavage of the SARS-CoV-2 spike protein by furin enhances binding capabilities and virus entry into various cell types. In COVID-19 patients, platelet count differs between mild and serious infections. Patients with mild symptoms have a slightly increased platelet count, whereas thrombocytopenia is a hallmark of severe COVID-19 infections. Low platelet count can be attributed to platelet apoptosis and the incorporation of platelets into microthrombi (peripheral consumption) and severe thrombotic events. The observed excessive formation of thrombi is due to hyperactivation of platelets caused by the infection. Various factors have been suggested in the activation of platelets in COVID-19, such as hypoxia, vessel damage, inflammatory factors, NETosis, SARS-CoV-2 interaction, autoimmune reactions, and autocrine activation. COVID-19 does alter chemokine and cytokine plasma concentrations. Platelet chemokine profiles are altered in COVID-19 and contribute to the described chemokine storms observed in severely ill COVID-19 patients.
Keywords: SARS-CoV-2; COVID-19; platelets; thrombosis; thrombocytopenia